A study on different variables on the distribution law of oil and gas diffusion concentration of internal floating roof tanks - JiChao Li; Xingjian Li; Dongjiang Yang; Yadong Zhang; Yakun Liu; XueXin Zhu; Cong Zhang; Shiwang Dang; Chuanbo Li; Yan Liu (Scientific Reports)
Abstract Internal floating roof tanks are used to store volatile, flammable, and explosive liquids, making the study of oil vapor diffusion concentration in the gas space of the internal floating roof tank critical for safety management. This study developed a computational fluid dynamics (CFD) model using CFD, based on the Realizable k-ε turbulence model to evaluate the effects of varying liquid levels. (low, medium, high) of the floating roof and external wind speeds on the oil vapor volume fraction. The results indicate that oil vapor volume fraction decreases as the roof rises, indicating that the expansion of the gas space leads to a more dispersed distribution of oil vapor. Additionally, the effect of external wind speed on the evaporation process is minimal and does not significantly influence the diffusion capacity of volatile oil vapor. This study evaluates the safety of vapor concentration relative to the explosion limits of gasoline and n-heptane, providing fundamental guidance for the safe management of storage tanks.